2010
DOI: 10.1159/000322049
|View full text |Cite
|
Sign up to set email alerts
|

FOXP3 Expression in Duodenal Mucosa in Pediatric Patients with Celiac Disease

Abstract: Objective: It was the aim of this study to evaluate the number of 2 lymphoid subpopulations, CD8+ cells and FOXP3+, in the duodenum mucosa from pediatric celiac patients. Methods: Tissue sections prepared from paraffin-embedded biopsies of the descending duodenum of 61 celiac patients with Marsh grade 1 (M1), M2 and M3 disease and biopsies from 21 age-matched non-celiac (NC) patients were immunohistostained with anti-CD8 or FOXP3 antibodies. Results: The histological Marsh grade correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 60 publications
4
10
1
1
Order By: Relevance
“…We also reported that the T-reg marker FOXP3 was elevated in untreated CD (Figure 14), which is in concordance with other reports [181,196,197]. The up-regulated FOXP3 levels were seen both at the mRNA and protein level in the Finnish study population, but also in the Swedish study population.…”
Section: Th17 and Treg Responses In CDsupporting
confidence: 92%
See 1 more Smart Citation
“…We also reported that the T-reg marker FOXP3 was elevated in untreated CD (Figure 14), which is in concordance with other reports [181,196,197]. The up-regulated FOXP3 levels were seen both at the mRNA and protein level in the Finnish study population, but also in the Swedish study population.…”
Section: Th17 and Treg Responses In CDsupporting
confidence: 92%
“…In addition to the elevated IFN- levels, active CD has been reported to be associated with elevated levels of IL-2 [183], IFN- [193], TNF- [183,194], IL-6 [194], IL-4 [183], IL-15 [180,195], FoxP3 [181,196,197], IL-10 [175,179,181], IL-17 [184,186,198], IL-21 [199], whereas the levels of IL-18 were diminished in active disease [181]. The results from the studies of intestinal cytokines are contradictory, since other studies have shown similar levels of several cytokines in CD patients and controls [184,189,200,201] [ 179,181,182,185,200].…”
Section: Development Of Cd/(molecular) Pathogenesismentioning
confidence: 99%
“…Those acquiring tolerance to the food show significantly higher levels of the FoxP3 gene expression than children with active food allergy [95]. However, whereas some studies showed normal FoxP3 levels in infants with milk and egg allergy, some others demonstrated FoxP3 + cells increasing in the duodenum of patients with untreated food allergy, even if these cells are not able to suppress the harmful immune response, indicated by the low FoxP3 transcript expression [96][97][98].…”
Section: Non-celiac Gluten Sensitivitymentioning
confidence: 99%
“…Previous works have reported that both Tregs and Th17 cells are involved in active CD. 19, 20, 21 Tregs perform an anti-inflammatory activity and can downregulate the immune response. Despite their suppressor activity on the immune response, Tregs are increased in the inflamed mucosa of active CD.…”
Section: Introductionmentioning
confidence: 99%
“…19, 22, 26, 28 Therefore, we compared the distribution of several subsets of T lymphocytes (Treg, Th17 and naïve CD62L cells) in both PB and in the duodenal mucosa of CD patients at diagnosis and after a GFD diet, as compared with non-CD controls. Finally, as T cells expressing the adhesion molecule CD103 are known to home in the intestine, we also evaluated CD103+ cells to get insights in the homing of T cells during the disease.…”
Section: Introductionmentioning
confidence: 99%